2016
DOI: 10.1038/lsa.2016.201
|View full text |Cite
|
Sign up to set email alerts
|

Functional optoacoustic neuro-tomography for scalable whole-brain monitoring of calcium indicators

Abstract: Non-invasive observation of spatiotemporal activity of large neural populations distributed over entire brains is a longstanding goal of neuroscience. We developed a volumetric multispectral optoacoustic tomography platform for imaging neural activation deep in scattering brains. It can record 100 volumetric frames per second across scalable fields of view ranging between 50 and 1000 mm3 with respective spatial resolution of 35–200 μm. Experiments performed in immobilized and freely swimming larvae and in adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 42 publications
0
113
0
3
Order By: Relevance
“…The same methodology is readily applicable for characterization of different sensory responses (e.g., due to somatosensory, paw, or whisker stimulations) and can be further combined with the recently demonstrated optoacoustic imaging of fast neuronal responses using calcium indicators, 11 thus shedding more light on the mechanisms of neurovascular coupling and the origins of neurological disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same methodology is readily applicable for characterization of different sensory responses (e.g., due to somatosensory, paw, or whisker stimulations) and can be further combined with the recently demonstrated optoacoustic imaging of fast neuronal responses using calcium indicators, 11 thus shedding more light on the mechanisms of neurovascular coupling and the origins of neurological disorders.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 Furthermore, by detecting spectroscopic changes in genetically encoded calcium indicators, functional optoacoustic neurotomography has shown promise for direct monitoring of fast neural activity. 11 To this end, optoacoustic microscopy and tomography have been successfully employed to monitor brain hemodynamic responses due to electrical stimulation 9,12 and superficial seizure activity in mice. [13][14][15] Real-time optoacoustic imaging of two-dimensional (2-D) cross-sections through the whole mouse brain is further possible with systems based on arrays of cylindrically focused transducers.…”
Section: Introductionmentioning
confidence: 99%
“…11b). GCaMP was shown to exhibit optoacoustically measurable variations in its extinction coefficient due to the influx of calcium ions into neurons [255]. The calcium-sensitive dye Arsenazo III has also been used to detect calcium concentration changes in other types of cells [256].…”
Section: Dynamic Contrast Enhancement Approachesmentioning
confidence: 99%
“…Genetically encoded calcium indicators (GECIs), and primarily the GCaMP family of indicators have become the workhorse tool for visualizing distributed activity across neuronal populations. In a very recent study, functional optoacoustic neuro-tomography (FONT) has successfully demonstrated imaging of calcium-sensitive protein GCaMP5G expressed in a transgenic zebrafish model [255]. The study established a very strong correlation between the fluorescence and optoacoustic activity-dependent signals of the indicator.…”
Section: Applications Enabled By Optoacoustic Visualization Of Multmentioning
confidence: 99%
“…Efforts are now underway to engineer these molecules at the genetic level 65 and express them heterologously as reporter genes. In addition, photoacoustic imaging, which combines diffuse optical excitation with acoustic readout for in vivo imaging applications 66, 67 , has engendered the development of optically absorbing molecules as reporter genes 6870 .…”
Section: Main Textmentioning
confidence: 99%